Cystatin C-Based Evaluation of Kidney Function of HIV-Infected Children in Benin City, Southern Nigeria - Moses Temidayo Abiodun; Nosakhare J. Iduoriyekemwen; Phillip O. Abiodun (International Journal of Nephrology)
Background. Human immunodeficiency virus (HIV) is now a confirmed risk factor for kidney disease with an increased burden in persons of African descent. Method. We measured the serum cystatin C levels of 205 ART-naive, HIV-infected children by an ELISA technique and compared them with the levels of apparently healthy children. Result. The mean ± SD serum cystatin C level of children with HIV infection was 1.01 ± 0.44 mg/L, significantly higher than the mean value in the control group, that is, 0.72 ± 0.20 mg/L (P=0.000). The mean ± SD cystatin C-based estimated GFR of children with HIV infection was 102.7 ± 31.0 mL/min/1.73 m2, significantly lower than 126.9 ± 28.5 mL/min/1.73 m2 in the control group, (P=0.014). A significantly higher proportion of HIV-infected children compared to controls had eGFR < 90 mL/min/1.73 m2 (21.5% versus 5.4%; P=0.00). The prevalence of chronic kidney disease (CKD) among the HIV-infected children was 10.7%. The cystatin C-based eGFR of the HIV-infected children ≥5 years old correlated positively with their CD4 count (r=0.23;  P=0.022). Conclusion. There is a high prevalence of CKD among HIV-infected children, requiring regular monitoring of their kidney function using a cystatin C-based method.